The Story of Algebraic Numbers in the First Half of the 20th Century From Hilbert to Tate - Narkiewicz, Władysław (Springer Monographs in Mathematics,, 2018)
The book is aimed at people working in number theory or at least interested in this part of mathematics. It presents the development of the theory of algebraic numbers up to the year 1950 and contains a rather complete bibliography of that period. The reader will get information about results obtained before 1950. It is hoped that this may be helpful in preventing rediscoveries of old results, and might also inspire the reader to look at the work done earlier, which may hide some ideas which could be applied in contemporary research.